Determining the time-dependent matrix potential in a wave equation from partial boundary data. Issue 16 (10th December 2021) - Mishra, Rohit Kumar; Vashisth, Manmohan
ABSTRACT: We study the inverse problem for determining the time-dependent matrix potential appearing in the wave equation. We prove the unique determination of potential from the knowledge of solution measured on a part of the boundary.